Understanding librarians : communication is the issue - Hull, Barbara; ScienceDirect eBooks (Witney : Chandos Publishing (Oxford) Ltd, 2011)
Aimed at professionals and trainee professionals within the library and information service (LIS) fields, this book reminds the reader of the frequently ignored communication-gulf between the professional and the layman, and in particular the lack of true communication between LIS professional and the user. It focuses especially on 'non-standard' users, such as non-native speakers or those with some disability. The author will provide accessible examples of good practice, assess their degree of success and suggest further ways to improve performance in information provision.
Promoting from within the serviceGood personal qualities for staff; Employing volunteers; Junior staff need the bigger picture too; Recognising individual members of staff; Notes; References; 14Self publicise; Sell your service!; The need to remind users; Integrating into your community; Satisfied users as ambassadors; Importance of names; Joining in; Publicise your achievements; Notes; References; 15Breaking down the library walls: responding to the needs of the Google generation; Background project 1; Pilot service: discussion; Background project 2; Implementation and pilot testing.
Includes bibliographical references and index.
Safari Books Online
Elsevier
Keywords: Libraries -- Public relations -- Great Britain; Communication in library science; Interpersonal relations; Libraries and community -- Great Britain; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Communication in library science; Interpersonal relations; Libraries and community; Libraries -- Public relations; Great Britain; Electronic books